O conhecimento pedagógico do conteúdo e a didática da geografia - Oliveira, José Ricardo de (2015)
This work aimed to analyze the didactic-pedagogical strategies used by four of Geography teachers, experienced and successful, involved in basic education in schools belonging to the Regional Center of Maringá, State of Paraná, in the final years of Elementary School and Secondary School. To understand how teachers organized their actions in the classroom, teachers whose practices need to lead students to a geographical education, we adopted as main theoretical reference the studies of Lee S. Shulman on the Knowledge Base, especially the Pedagogical Knowledge Content - CPC, that teachers need to do their teaching and the Pedagogical Reasoning and Action Process that portrays how teacher's knowledge are driven, related and built during the process of teaching and learning. In this perspective, we understand that teaching through the development of Pedagogical Content Knowledge, transforms the specific knowledge in educational content, making them more comprehensible and meaningful to the lives of students. Therefore, the methodology adopted for this research focused on the qualitative aspects, because the focus of this study is to understand the ways in which teachers give meaning to their work and act in their professional contexts. Individual and semi-structured interviews and classroom observations were our methodological procedures used in the field research, the analysis of the data was performed by the methodology of content analysis, because it helps the researcher to reinterpret messages and reach a deeper understanding of the statements and actions of teachers in the classroom. Thus, it was possible to understand that the investigated teachers that sued and mobilized their dominated knowledge and which often have consciousness of their own action, working the geographic content in coordination within an articulated sequence that included, in most cases, the involvement of student in the learning proposal. The survey results make it clear that when teachers sue and mobilize the CPC in their classes, the teaching of geography is enhanced, facilitating the understanding and the importance of such content for students as well. It was also found that the development of the CPC is what differentiates a successful teacher of that other professional that only dominates their discipline. But often, in practice, to many teachers there are not proportionate the necessary conditions - continuing education, teaching materials, school infrastructure etc. - to adequately respond to what is expected of them. However, many teachers have extensive baggage of knowledge produced in their day-to-day, but which are not systematized. Thus many good pedagogical practices in the classroom are lost for lack of records and socialization of these experiences, which could be used to guide the work of beginning teachers and thus contribute to their training and the need to value and enhancement the work of teaching.